Initiation of Eco-Islamic Boarding School-Based Food Garden at Al Bayan Islamic Boarding School Sendangrejo Minggir Sleman - Triyono Triyono; Zuhud Rozaki; Mamnuah; Nur Faidati (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Food garden activities based on religious values are a special form of community development in environmental management. This activity is considered quite effective because the awareness or education is carried out by religious/community leaders who are trusted and respected by the community. Mass mobilization activities are also easier because the activities are carried out in the pesantren environment where they meet at any time to carry out worship and education at the Islamic boarding school. Partners for community service, namely the Al Bayan Islamic Boarding School in Tobayan Hamlet, Sendangrejo Minggir, Sleman, DIY. The partners' problems are as follows: low public awareness and knowledge of the importance of managing a clean and productive Islamic boarding school environment, land has not been utilized as a source of cheap healthy (vegetable and animal) food for students. Based on these problems, this community service aims to help manage the environment of Islamic boarding schools and provide healthy food through an eco-Islamic boarding school based food garden. Through assistance in the management of eco-Islamic boarding schools based food gardens, the planned solutions are: First, the Focus Group Discussion (FGD) aims to identify in more detail related to environmental management through eco-Islamic boarding schools based food gardens and the needs of partners. Second, Counseling and recitation of eco-Islamic boarding school-based food gardens is carried out to increase awareness and knowledge in environmental management through eco-Islamic boarding school-based food gardens. Third, training on organic fertilizers and cultivating vegetables and ornamental plants to provide healthy food.